An overview on extenders used in ram sperm cryopreservation - Sevilla, Francisco (2024)
Introduction. One of the most critical methods for improving domestic animal reproduction is sperm cryopreservation. To achieve the best results, this complex process requires the meticulous balance of numerous variables. Sperm cryopreservation is an essential technique in programs that improve breeding and conservation for many species, especially small ruminants. In this case, genetic material from a limited number of exceptional sires can be used to breed a large number of female sheep. Objective. To analyze the current advances in extenders used in ram sperm cryopreservation. Development. In rams, spermatozoa have a lower intramembrane cholesterol-to-phospholipid ratio than other species, making them more susceptible to cryopreservation damage than other livestock species. Adequate freezing and thawing can prevent metabolic and structural damage to ram sperm cells, a goal that has not yet been achieved. The success of the sperm freezing process depends on several factors, such as freezing/thawing rate, equilibration time, spermatozoa, and the composition of medium surrounding spermatozoa, among others. In this sense, sperm extender is one of the most critical factors in the cryopreservation process. Conclusions. The vulnerabilities of ram sperm to cryogenic stress poses challenges to maintaining viability after thawing and achieving consistently high fertility rates. Further research to refine supplementation strategies, optimize freezing protocols, and explore novel cryoprotectants is essential to overcome these challenges and enhance the efficacy of ram semen cryopreservation to improve reproductive outcomes in ovine breeding programs.